Financing Environmental Services in Developing Countries - Sander, Klas; Cranford, Matthew (World Bank, Washington, DC, 2017)
Current international financing (primarily ODA) for environmental services in developing countries is very roughly estimated to be upwards of $21 billion annually (not including climate change financing), but additional resources on the order of tens, if not hundreds, of billions of dollars are needed. In 2009, environmental ODA was estimated at $18 billion with a few billion more delivered through philanthropic and market-based financing channels. Although there are only a few studies of the additional financing needed, and those are relatively narrow in scope, the estimates that are available clearly indicate that significantly higher levels of finance still need to be reached. Additionally, the impacts of environmental finance on environmental sustainability and development objectives are poorly understood. Systematic reviews of previous experience, and standardized monitoring in the future, would support the countries and projects monitored, while also providing important lessons for the broader development and environment communities.